Ubiquitous Collaborative Learning Applications: Driving Gender-Inclusive Success in Computer Education - Thongkoo, Krittawaya; Daungcharone, Kannika (Journal of Applied Informatics and Technology, 2026)
This study explores the transformative potential of ubiquitous collaborative learning applications in fostering gender-inclusive success in computer education. Persistent gender disparities in STEM fields, particularly in computing, highlight the need for innovative educational approaches that ensure equitable access and engagement. This research evaluates how these applications enhance learning achievement and perceptions equitably across genders, providing a promising pathway to address long-standing challenges in education. A mixed-methods approach was employed, involving 226 undergraduate computing students from northern Thailand. Data collected through pre- and post-tests and surveys revealed significant improvements in learning achievement for the experimental group, with no notable gender differences in outcomes. Additionally, students in the experimental group reported higher satisfaction with the application's user interface, perceived usefulness, ease of use, and overall learning experience than those in the control group. The findings underscore the capacity of ubiquitous collaborative learning applications to support inclusive and equitable education, addressing gender disparities while improving educational outcomes. The implications of this study are significant, highlighting the importance of leveraging innovative educational technologies to foster engagement, reduce inequities, and prepare students for the demands of the digital era.